Neuroprotective Role of a Novel Copper Chelator against Aβ42 Induced Neurotoxicity. (18th September 2013) - Singh, Sandeep Kumar; Sinha, Priti; Mishra, L.; Srikrishna, S.
Abstract : Alzheimer's disease (AD) is a progressive neurodegenerative disease and associated with the extracellular deposits of amyloid- β peptide in hippocampus region. Metal ions like Cu, Fe and Zn are known to associate with the amyloid beta (A β ) at high concentration and interaction of these ions with soluble and aggregated forms of A β peptide help in development of AD. Here we showed Cu mediated neurotoxicity in the eye tissues of transgenic Drosophila expressing human amyloid β and its rescue through a novel Cu chelator. In this context, we have synthesised and characterized the compound L 2, 6-Pyridinedicarboxylic acid, 2, 6-bis[2-[(4-carboxyphenyl) methylene] hydrazide] by Mass spectra (MS) and Elemental analysis (EA). The Cu chelation potential of the compound L is tested in vivo in Drosophila . Oral administration of Copper to the transgenic larvae resulted in severe degeneration in eye tissues, which was rescued by the supplementation of compound L. The levels of anti-oxidant markers like SOD and MDA were measured in compound L treated flies and found a significant rescue (P < 0.001 ). Further rescue of the eye degeneration phenotypes as revealed by SEM affirm the role of copper in A β toxicity. Hence, use of compound L, an amidoamine derivative, could be a possible therapeutic measure for A β induced neurotoxicity.